The Survival of Family Farms: Socioemotional Wealth (SEW) and Factors Affecting Intention to Continue the Business - Manel Plana-Farran; José Luis Gallizo (Agriculture, 2021)
This article addresses the problem of succession in family farms in a context of generational change. Family businesses are characterized by their long-term orientation and by having a positive effect through environmental goals that remain in place generation after generation. The general increase in average age among farmers is seen as a barrier to more sustainable land use, and the survival of family farming therefore depends on the availability of a successor in the family. Socioemotional wealth (hereafter, SEW) is understood as the affective endowment of family members. This study adopts the SEW dimensions conceptually validated to analyse the effects of psychological and socioeconomic factors on potential successors’ intentions. The results of a survey administered to students attending agricultural schools in Catalonia show that intentions to assume the management and ownership of the family farm increase in line with individuals’ interest in creating their own business, their ability to take over the farm, and their emotional inclination to continue the family legacy. In addition, SEW was measured in relation to the potential successor and not the incumbent, as has typically been the case in previous work, bringing this important research subject as a principal actor. Finally, an empirical validation of a short FIBER scale, i.e., REI scale, was obtained that relates individuals’ intentions to succeed the family farm to the socioemotional wealth of business families, testing suitability of the REI scale as a measure of intention to succeed.